Evaluation of two new methods for routine measurement of alkaline phosphatase isoenzymes. Issue 1 (January 1992) - Day, A P; Saward, S; Royle, C M; Mayne, P D
Abstract : AIMS: To evaluate the performance of two new methods for the analysis of alkaline phosphatase (ALP) isoenzymes designed for use in the routine chemical pathology laboratory: pre-incubation with neuraminidase before agarose electrophoresis; and selective precipitation of the bone isoenzyme with wheat germ agglutinin (WGA). METHODS: Serum samples from 39 patients were analysed. Seventeen were from patients with liver disease, eight from patients with bone disease, and 14 from patients with normal ALP activity and no evidence of liver or bone disease. The two new methods were compared with the established method, wheat germ agglutinin affinity electrophoresis. RESULTS: There was good correlation between the neuraminidase and WGA electrophoretic methods. The WGA precipitation method showed negative interference in the measurement of bone isoenzyme activity in samples containing biliary alkaline phosphatase. Both the new methods had advantages of speed and simplicity over the existing method, but cost per test was considerably higher. CONCLUSIONS: The neuraminidase electrophoretic method is a satisfactory alternative to the WGA affinity electrophoretic method, although it is more expensive. The WGA precipitation method cannot be recommended for use with serum samples from patients with suspected liver disease.